Nterleukin-4 responsive dendritic, macrophage/neutrophil cells are dispensable for host resistance against Leishmania Mexicana infection in mice - Ong'ondo, Bernard Osero (Department of Clinical Laboratory Sciences, 2022)
Studies have shown that the protection against L. mexicana infection is potentiated by a type 1 response, driven by IL-12 production by dendritic cells. In contrast, IL-4 and IL-13 cytokines are associated with susceptibility to L. mexicana causing cutaneous leishmaniasis. This has been demonstrated in studies involving BALB/c mice deficient in IL-4, IL-13, and IL-4Rα infected with L. mexicana. To determine the specific cell in IL-4Rα-/- BALB/c mice that contribute to the control of L. mexicana infections, studies on cell-specific IL-4Rα deficient mice need to be investigated. IL4Rα-CD4+T deficient mice revealed sex-dependent protection from L. mexicana infection, suggesting the critical role of non-lymphocyte cells in conferring protection against L. mexicana amastigote infection. Macrophage/neutrophil-specific IL-4Rα deficient mice are protected from L. major infection in the footpad. Surprisingly, this mouse strain infected in the base of the tail failed to control L. mexicana amastigote infection. Nonetheless, IL-4Rα-DC deficient mice were hyper-susceptible to L. major infection. This conundrum suggests that different Leishmania species, site of infection, and developmental stages of parasite dictate the outcome of the disease. Here, mice with a deficiency of IL-4Rα signaling on DCs and macrophage/ neutrophil cells were subcutaneously infected with L. mexicana promastigotes in the footpad, and skin lesion progression was measured, and the clinical phenotype was evaluated by investigating both humoral and cellular immune responses. Mouse strains had similar footpad lesion progression, parasite loads, humoral responses, expansion of CD4+ and CD8+ T cells, their activation, memory phenotypes, and infiltration of DCs, macrophages, and neutrophils into the lymph nodes compared to their littermate IL-4Rα-/lox controls. Interestingly, IL‐12p70 and IL‐10 produced by BMDCs and BMDMs were similar. Nevertheless, nitrite/urea production was not affected. Together, this study suggests that, unlike L. major, IL-4Rα signaling on DCs and macrophage/ neutrophil cells does not contribute to the susceptibility or resistance to BALB/c mice to infection with L. mexicana.